The Marching Band's Musical Activities as a Learning Space for Soft Skills among Vocational Engineering Students at PEM Akamigas Cepu - Givan Sonya Gani; Syahrul Syah Sinaga (Catharsis, 2025)
Marching bands as community musical activities have pedagogical potential in the development of soft skills, but studies on this topic are still relatively limited in the context of engineering vocational education. This study aims to understand and identify musical activities in marching band activities as a learning space for soft skills for engineering vocational students at the Politeknik Energi dan Mineral (PEM) Akamigas. The focus of the study is directed at the forms of musical activities that take place in marching bands and their role in facilitating the development of soft skills through collective, structured, and sustainable musical practices. This study uses a qualitative approach with a case study design that has ethnographic tendencies. Data were collected through participatory observation, in-depth interviews with marching band members, coaches, and advisors, as well as document studies. Data analysis was conducted thematically by linking field findings to Robles' soft skills framework and Temmerman's theory of community musical activities. The results of the study indicate that marching band musical activities, such as routine practice, playing instruments, marching, and group coordination, serve as an effective non-formal learning space for developing students' soft skills, including discipline, teamwork, communication, leadership, and responsibility. These findings confirm that community musical activities have pedagogical relevance as a medium for contextual soft skills learning in engineering vocational education.